The life of William Cobbett - Cole, G. D. H. (George Douglas Howard), 1889-1959 (Cole, G. D. H. (George Douglas Howard), 1889-1959. Selections, 2010)
This volume is representative of the historical works of a particular period (1923-29) when there was a hiatus in the output of Cole the theoretician. It is an extraordinary contribution to labour history and is among the finest of his historical works.